Lipid metabolism disorders of hybrid grouper (♀Epinephelus fuscointestinestatus × ♂E. lanceolatu) induced by high-lipid diet - Suo, Xiangxiang; Yan, Xiaobo; Tan, Beiping; Pan, Simiao; Li, Tao; Liu, Hao; Huang, Weibin; Zhang, Shuang; Yang, Yuanzhi; Dong, Xiaohui (Frontiers in Marine Science, 2022)
This study investigated the effect of lipid levels on growth, body composition, lipid metabolism enzymes activity and related genes expression in hybrid grouper (♀Epinephelus fuscointestinestatus × ♂E. lanceolatu). Three diets with different lipid levels of 6% (low-lipid feed, LF), 11% (medium-lipid feed, MF) and 16% (high-lipid feed, HF) were designed and each diet was fed to triplicate groups of 30 fish each (6.73 ± 0.00g) for eight weeks. The results revealed the following. 1) The WGR, SGR, PER and the lowest FCR values were found in the HF group. There was no significant difference in the SR among the groups (P > 0.05). 2) CF, HSI, VSI increased with increasing dietary lipid. 3) Crude lipid content in the whole-body and muscle increased significantly as the dietary lipid level increased (P < 0.05). 4) Principal component analysis of fatty acids showed that (∑n-3PUFA)/(∑n-6PUFA) was significantly higher in the HF group than in the other two groups (P < 0.05). 5) Biochemical serum indexes showed higher TG, TC, AKP and LDL-C levels but lower HDL-C level in the HF group. 6) Liver lipid metabolism enzymes activity and biochemical indicators showed that fish fed the MF diet had higher LPL, HL and ATGL activity but lower FAS activity and VLDL-C level. 7) The relative expression levels of lipoprotein lipase (lpl), adipocyte-type fatty acid-binding protein (a-fabp), liver-type fatty acid-binding protein (l-fabp), heart-type fatty acid-binding protein (h-fabp) and hormone-sensitive lipase (hsl) genes in the fish liver were higher in the MF group with increasing dietary lipid (P < 0.05), while the fatty acid synthase (fas) gene was expressed at lower relative level (P < 0.05). 8) Histological oil-red sections of the liver showed that fish in the HF group had larger and more hepatic lipid droplets than those fed the other diets. It was concluded that fish fed the HF diet had better growth performance but this diet was not conducive to the progress of lipid metabolism, resulting in lipid accumulation and affecting the quality of the fish. This study provides useful information for the formulation of environmentally friendly and cost-effective diets for hybrid grouper.